Manipulating carbohydrate availability between twice-daily sessions of high-intensity interval training over 2 weeks improves time-trial performance - Cochran, A. J. R.; Myslik, F.; MacInnis, M. J.; Percival, M. E.; Bishop, D.; Tarnopolsky, M. A.; Gibala, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Commencing some training sessions with reduced carbohydrate (CHO) availability has been shown to enhance skeletal muscle adaptations, but the effect on exercise performance is less clear. We examined whether restricting CHO intake between twice daily sessions of high-intensity interval training (HIIT) augments improvements in exercise performance and mitochondrial content. Eighteen active but not highly trained subjects (peak oxygen uptake [VO2peak] = 44 ± 9 ml/kg/min), matched for age, sex, and fitness, were randomly allocated to two groups. On each of 6 days over 2 weeks, subjects completed two training sessions, each consisting of 5 × 4-min cycling intervals (60% of peak power), interspersed by 2 min of recovery. Subjects ingested either 195 g of CHO (HI-HI group: ~2.3 g/kg) or 17 g of CHO (HI-LO group: ~0.3 g/kg) during the 3-hr period between sessions. The training-induced improvement in 250-kJ time trial performance was greater (p = .02) in the HI-LO group (211 ± 66 W to 244 ± 75 W) compared with the HI-HI group (203 ± 53 W to 219 ± 60 W); however, the increases in mitochondrial content was similar between groups, as reflected by similar increases in citrate synthase maximal activity, citrate synthase protein content and cytochrome c oxidase subunit IV protein content (p > .05 for interaction terms). This is the first study to show that a short-term "train low, compete high" intervention can improve whole-body exercise capacity. Further research is needed to determine whether this type of manipulation can also enhance performance in highly-trained subjects.